Erythema nodosum as the initial presentation of leprosy in a 15-year-old boy: a case report on Ethiopia’s persistent elimination challenges - Tukeni, Kedir Negesso; Aga, Tadele Molla; Abadiko, Elias Ababulgu; Mamo, Idosa Taso; Woyimo, Tamirat Godebo; Biru, Eyob Tarekegn; Abafogi, Abdo Kedir; Gudina, Esayas Kebede (Frontiers in Medicine, 2025)
Leprosy remains a significant public health concern in Ethiopia, with challenges in timely diagnosis and management contributing to disabilities. This case report details a 15-year-old boy who presented with diffuse nodular and bullous skin lesions, peripheral neuropathy, and systemic symptoms, ultimately diagnosed with multibacillary leprosy confirmed by a positive skin smear for acid-fast bacilli. A 15-year-old immunocompetent boy presented to the emergency department with a 2-week history of diffuse, non-pruritic skin lesions, joint swelling, numbness, and tingling sensation. The patient was febrile on arrival. Physical examination revealed an erythematous nodular skin lesion over the face and hand bilaterally and a non-blanching bullous lesion over the right leg. The left hand was swollen and tender to touch, with a superficial collection, suggestive of an abscess. There was also a hypopigmented skin lesion over the medial aspect of the left leg and thigh bilaterally with loss of sensation. There were bilateral ulnar and radial nerve enlargement, saddle nose, and tenderness at the olecranon area. The skin smear was positive for acid-fast bacilli. The patient was initially treated with corticosteroids and antibiotics, followed by referral for multidrug therapy, and was advised for further follow-up for treatment response. The case describes the critical role of early recognition and multidisciplinary management in leprosy, particularly in endemic areas. The complexity of the presentation demonstrates the need for ongoing vigilance among healthcare providers. Public health initiatives aimed at improving diagnostic capabilities and expanding leprosy services are vital for reducing the disease burden in countries such as Ethiopia.